Baseline survey of marine sediments collected from the Kingdom of Bahrain: PAHs, PCBs, organochlorine pesticides, perfluoroalkyl substances, dioxins, brominated flame retardants and metal contamination. (December 2020) - Bersuder, P.; Smith, A.J.; Hynes, C.; Warford, L.; Barber, J.L.; Losada, S.; Limpenny, C.; Khamis, A.S.; Abdulla, K.H.; Le Quesne, W.J.F.; Lyons, B.P.
Abstract: A baseline survey of sediment contamination was undertaken at 14 locations around the coastline of Bahrain in May 2017, followed by a focused survey of 20 sites, in November 2019. Samples were assessed for industrial pollutants, including metals, PAHs and a suite of organohalogen compounds. The data generated indicated that levels of chemical contaminants were generally low and did not pose a toxicological risk when assessed against commonly applied sediment quality guidelines (SQG). The highest concentrations of PAHs and PCBs were identified in samples collected at coastal sites adjacent to a refinery area known to contain a diverse mix of industry. Tubli Bay, a heavily stressed small bay receiving high loads of sewage effluent, was also identified as an area warranting further investigation with elevated concentrations of BDE209, PFOS and metal contamination. Such data provides a useful baseline assessment of sediment contamination, against which management control measures can be assessed. Highlights: Contaminant levels in general were low and indicative of clean environments. Hotspots of PAHs, PCBs, Dieldrin and PBDEs contamination close to the Refinery Area. BDE209 and ∑DDT exceeded existing international sediment quality guidelines in Tubli Bay. First regional report of PFAS in sediment, with PFOS prevalent in Tubli Bay.